Causal Relationship between Economic Growth, Financial Deepening, Foreign Direct Investment and Innovation: Evidence from China - Islam, Mollah Aminul; Liu, Haiyun; Khan, Muhammad Asif; Reza, Sultanuzzaman MD; Yahia, Yassin Elshain; Nasrin, Layla (Asian Economic and Financial Review, 2018)
This research examines the cointegration and causal relationship between economic growth, financial deepening, foreign direct investment and innovation in the context of China. The empirical results of the ARDL Bounds test to cointegration and VECM Granger causality validate the cointegration and causal association among variables. The study offers policy implication to bring more depth to the financial system to elevate potential innovative environment through FDI. Moreover, to boost real growth through the creation of spillover effects and to enrich the absorptive capacity, the policymakers need to pay attention to financial institutions access, depth and efficiency.